Alternative way in reducing car cabin temperature using portable car cooling system (Car-Cool) - Yaakub, Muhamad Faizal; Basar, Mohd Farriz; Musa, Marina; A. Razik, Normariani (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2013)
Until now,car owners especially in ASEAN countries are facing problems where the temperature is too hot in the car when they park their cars under the scorching sun. Various problems will arise caused by this situation.In this paper,the design and development of portable car cooling system is described briefly.Electrical Motor, rechargeable battery,Peltier cell,rotating cloth;these are the components that have been combined in order to complete a simple cooling system.Based on the experimental activities’ result,it is proven that the conducted research has a positive impact where it has successfully maintain the temperature inside the car at room temperature.For comparison,the temperature inside the car can achieve up to 70°C without the proposed system.Furthermore,the simple proposed system provides comfort to users due to its capability in improving the quality of air and moisture in the car’s cabin.